Genomic dynamics of species and mobile genetic elements in a prolonged blaIMP-4-associated carbapenemase outbreak in an Australian hospital - Kizny Gordon, A; Phan, HTT; Lipworth, SI; Cheong, E; Gottlieb, T; George, S; Peto, TEA; Mathers, AJ; Walker, AS; Crook, DW; Stoesser, N (Oxford University Press, 2020)
Background Hospital outbreaks of carbapenemase-producing organisms, such as blaIMP-4-containing organisms, are an increasing threat to patient safety.